Rancang Bangun Lengan Robot Mikrokontroller Dengan Kendali Smartphone Berbasis Internet of Things - Umar Alifiah; Relita Buatin; Katen Lumbanbatu (Indonesian Journal of Education And Computer Science, 2023)
This research discusses the design and implementation of a robot arm that is controlled via smartphone using the Internet of Things (IoT) concept. This robotic arm is controlled using a microcontroller connected to the internet. The aim of this research is to develop a system that allows users to easily control the movement of the robot arm via a specially designed smartphone application. At the design stage, the microcontroller is programmed to control the motors that drive the robotic arm joints. Communication between the smartphone and the robot arm is implemented via a network communication protocol, so the user can give commands via an intuitive application interface. The use of IoT technology allows this robot arm to be controlled remotely via the internet, opening opportunities for use in various contexts, such as use in production, education or even entertainment environments. Test results show that the robotic arm can automatically carry out repetitive tasks with a high level of accuracy. This advantage can increase productivity in the production process and reduce the potential for human error. In addition, robots can operate in environments that are potentially dangerous to humans, such as toxic, radioactive or extreme temperature (hot or cold) areas. This capability effectively reduces the risk of human exposure to these potential hazards